核桃仁内种皮中缩合单宁多聚体的分离 及其抗氧化活性分析Isolation and antioxidant activity analysis of condensed tannin polymers in walnut pellicle - 崔茂凯1,2，黄海涛3，李庆杨1，沈丹玉1，肖鹏飞3，刘毅华1 CUI Maokai1,2, HUANG Haitao3, LI Qingyang1, SHEN Danyu1, XIAO Pengfei3, LIU Yihua1 (Zhongguo youzhi)
为给核桃资源的高值化利用提供参考，以核桃仁内种皮为原料，通过70%甲醇溶液（含0.5%冰乙酸）萃取，Sephadex LH-20 葡聚糖凝胶层析柱分离，经不同体积分数的甲醇溶液梯度洗脱得到13个核桃仁内种皮缩合单宁多聚体分离物（F1~F13），以VC为标样，对这13个分离物的体外抗氧化活性进行分析。结果表明：采用甲醇溶液（体积分数40%~75%）梯度洗脱方法可从核桃仁内种皮中分离出缩合单宁二聚体（DP2）至七聚体（DP7）；DP2和缩合单宁三聚体（DP3）的洗脱甲醇溶液体积分数在40%~60%，缩合单宁四聚体（DP4）和其他3种高聚体的洗脱甲醇溶液体积分数在60%~75%；优化洗脱操作后 DP2 和 DP3可被高效分离，DP2洗脱率超过80%，其中F2、F3和F4中得到DP2，总含量超过1.40 mg/g，F5 和 F6中得到 DP3，含量分别为 0.66 mg/g和 0.59 mg/g；F1~F13都具有良好的抗氧化活性，其中以DP2为主的F4抗氧化活性最高，铁离子还原能力（FRAP） 和 DPPH自由基清除能力分别为（17.22±0.68） mg/g和（24.36±0.73） mg/g。综上，采用梯度洗脱方法可实现缩合单宁多聚体的洗脱分离，可从核桃仁内种皮中分离出 DP2和DP3。:To provide a reference for the high-value utilization of walnut resources, walnut pellicle was used as raw material and extracted with a 70% methanol solution (containing 0.5% acetic acid). The extract was separated with a Sephadex LH-20 dextran gel column and subjected to gradient elution with different volume fractions of methanol solution to obtain 13 fractions of condensed tannin polymers (F1-F13). The in vitro antioxidant activity of these 13 fractions were analyzed using vitamin C as the standard sample. The results indicated that the gradient elution method with methanol solution (volume fraction 40%-75%) could successfully separate condensed tannin dimers (DP2) to heptamers (DP7) from walnut pellicle. The elution volume fractions for condensed DP2 and trimers (DP3) ranged from 40% to 60%, while the elution volume fractions for tetramers (DP4) and three other higher polymers were between 60% and 75%. After optimizing the elution process, efficient separation of DP2 and DP3 was achieved, with the elution rate of DP2 exceeding 80%. DP2 was isolated from elution fractions F2, F3, and F4, with a tatal content exceeding 1.40 mg/g, while DP3 was obtained from fractions F5 and F6, with contents of 0.66 mg/g and 0.59 mg/g, respectively. All fractions exhibited good antioxidant activity, with F4, primarily containing DP2, showing the highest antioxidant activity, measured by ferric ion reducing ant ioxidant power (FRAP) and DPPH methods as (17.22±0.68) mg/g and (24.36±0.73) mg/g, respectively. In conclusion, the gradient elution method enables the effective separation of condensed tannin polymers, allowing for the isolation of DP2 and DP3 from walnut pellicle.